2012
DOI: 10.1259/bjr/30878012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the echo intensity of the median nerve and flexor muscles of the forearm in the young and the elderly

Abstract: Objectives: Musculoskeletal structures often appear brighter on imaging in the elderly, which makes it difficult to accurately delineate a peripheral nerve during ultrasound-guided regional anaesthetic procedures. The echo intensity of skeletal muscles is significantly increased in the elderly. However, there are no data comparing the echo intensity of peripheral nerves in the young and the elderly, which this study was designed to evaluate. Methods: 13 healthy, young volunteers (aged ,30 years) and 11 elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
4
19
0
1
Order By: Relevance
“…Ultrasound visibility of the lumbar paravertebral structures in our patients was also rated as "average" and was poorer than what we have previously observed in young volunteers. 9 Age-related changes in musculoskeletal structures, particularly in the elderly (>60 years), can reduce the contrast between a peripheral nerve and its surrounding muscles 20 and can adversely affect the quality of ultrasound images. 21 In conclusion, we have described a technique of performing USG LPB using the PMTS-ITS ultrasound scan window in a cohort of patients with low BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound visibility of the lumbar paravertebral structures in our patients was also rated as "average" and was poorer than what we have previously observed in young volunteers. 9 Age-related changes in musculoskeletal structures, particularly in the elderly (>60 years), can reduce the contrast between a peripheral nerve and its surrounding muscles 20 and can adversely affect the quality of ultrasound images. 21 In conclusion, we have described a technique of performing USG LPB using the PMTS-ITS ultrasound scan window in a cohort of patients with low BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al evaluated the EIs of 40×40-pixel ROIs around the forearm flexor muscles and reported that the superficial tissue EI values were significantly greater than those of deeper tissues in young subjects but that no such difference was observed in elderly subjects 19. Similarly, in this study, the RF EI value, which is located more superficially than VI EI, was significantly greater than VI EI in the young subjects but not in the elderly subjects (Figure 1; Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The sonographic examinations were performed by a single investigator (with more than 10 years of experience in sonography) using the same ultrasound system (Micro‐Maxx version 3.1; SonoSite, Inc, Bothell, WA) with no auto‐gain or compound imaging facility and a high‐frequency linear array transducer (HFL38; 13–6 MHz, 38‐mm footprint). The ultrasound system settings were standardized for every participant as previously described 1 . This process included setting the delta key in the ultrasound system to reset to factory defaults to ensure that the initial gain was the same for every participant at the start of the sonographic examination after booting the ultrasound system.…”
Section: Methodsmentioning
confidence: 99%
“…Using computer‐assisted grayscale analysis, we recently demonstrated that the echo intensity of the median nerve at the forearm is significantly increased, and there is a loss of contrast between the median nerve and the surrounding muscles, in the elderly 1 . Age‐related reductions in the number, diameter, and average density of nerve fibers 2 , 3 and an increase in connective tissue elements 4 within a peripheral nerve, particularly after the sixth decade of life, may explain these findings 1 . However, echo intensity is a global measure of the total brightness of the pixels (gray scale) in a sonogram and does not take into account its spatial distribution.…”
mentioning
confidence: 99%